A Million Pictures Magic Lantern Slides in the History of Learning. - Dellmann, Sarah (Indiana University Press, 2020)
Authors of this collection of essays will include Richard Crangle, Sarah Dellmann, Ine van Dooren, Claire Dupré La Tour, Jenny Durrant, Francisco Javier Frutos Esteban, Anna Katharina Graskamp, Emily Hayes, Erkki Huhtamo, Martyn Jolly, Joe Kember, Frank Kessler, Machiko Kusahara, Sabine Lenk, Vanessa Otero, Carmen López San Segundo, Ariadna Lorenzo Sunyer, Daniel Pitarch, Jordi Pons, Montse Puigdeval, Angélique Quillay, Angel Quintana Morraja, Nadezhda Stanulevich, Jennifer Tucker, Kurt Vanhoutte, Márcia Vilarigues, Joseph Wachelder, Artemis Willis, Lee Wing Ki, Irene Suk Mei Wong, and Nele Wy.